2004
DOI: 10.1002/jso.20041
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of cytosolyc cathepsin D content in resectable gastric cancer

Abstract: The present study demonstrates the presence of higher Cath-D content in gastric carcinomas than in adjacent non-neoplastic mucosa, and that high intratumor Cath-D levels identify a subgroup of resectable gastric cancer patients with a high probability of relapse as well as worse survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In the present study we have evaluated the potential relationship between LBVI and several new biological parameters from gastric carcinomas recently associated with tumoral aggressiveness and poor prognosis, such as the tyrosine kinase receptors c-erbB-2 (Garcia et al 2003a;Vizoso et al 2004b) and EGFR (Garcia et al 2003b), the proteolytic enzymes cathepsin D (Manuel Del Casar et al 2004) and tPA (Raigoso et al 2000), the spasmolytic peptide pS2 (Suarez et al 2001;Dhar et al 2003) or the extracellular proteoglycan hyaluronic acid (Vizoso et al. 2004a).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study we have evaluated the potential relationship between LBVI and several new biological parameters from gastric carcinomas recently associated with tumoral aggressiveness and poor prognosis, such as the tyrosine kinase receptors c-erbB-2 (Garcia et al 2003a;Vizoso et al 2004b) and EGFR (Garcia et al 2003b), the proteolytic enzymes cathepsin D (Manuel Del Casar et al 2004) and tPA (Raigoso et al 2000), the spasmolytic peptide pS2 (Suarez et al 2001;Dhar et al 2003) or the extracellular proteoglycan hyaluronic acid (Vizoso et al. 2004a).…”
Section: Discussionmentioning
confidence: 99%
“…Although we have yet to complete the validation that the other six proteins using the same approach as described for CK19, a brief review of the published literature suggest their potential involvement in breast tumor development [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54]. Our research on breast cancer has been prioritized to confirm this concept experimentally and to define the functions of these proteins and to study their interrelationship in the malignant breast tissue microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Cathepsin D is up-regulated in many types of tumorigenesis [48] and down-regulated in a hepatoma revertant cell line [49]. Patients with lower levels of cathepsin D had better survival rates than those with intermediate or high cathepsin D tumor content [50]. Ikeguchi et al [51] reported that cathepsin D expression is associated with p53 abnormality in oesophageal squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Cathepsin D (CATD) was the best performing variable (AUC: 0.648) out of them. The level of CATD in gastric carcinomas represents poor prognosis 26 . NCAM1 (CD56) is a well-known surface marker of immune cells.…”
Section: Discussionmentioning
confidence: 99%